Penerapan Form Permintaan Barang oleh Bagian Kasir Sebagai Instrumen Pengawasan dan Optimalisasi Realisasi Anggaran Perusahaan ABC - Dimas Rafi Parama Putra; Tituk Diah Widajantie (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
This study aims to analyze the implementation of the Goods Request Form (FPB) by the cashier department as a tool for supervising and optimizing budget realization in Company ABC. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data were analyzed thematically to identify patterns and relationships between the use of FPB and the effectiveness of budget supervision. The findings indicate that the use of FPB strengthens internal control, reduces procurement inefficiencies, and enhances transparency and accountability in corporate budget management. These results imply that integrating procurement procedures with internal control systems through FPB can serve as an effective strategy in financial management. Therefore, it is recommended that the company continue to develop and periodically evaluate FPB implementation to ensure alignment with budgetary and operational goals.